Dielectric and piezoelectric properties of PZT-silica fume cement composites - A. Chaipanich (2018)
PZT-silica fume cement (PZT-SFC) composites were produced using PZT (at 50% and 60% by volume) and silica fume cement (cement containing silica fume of 5% and 10% by weight). PZT-Portland cement with no silica fume was also produced to allow comparison of the results. Dielectric constants of PZT-SFC composites are found to be higher than that of PZT-PC composite where εrvalue was found to increase with increasing SF content (εrvalues of composite with SF at 0%, 5% and 10% are 117, 125 and 178, respectively). PZT-SFC composites were successfully poled and d33results of PZT-SFC composites (d33= 18 pC/N) were found to be marginally higher than that of PZT-PC composite (d33= 17 pC/N). SEM micrograph also shows a dense matrix of SFC hydration product surrounding the PZT particles. From the results, these PZT-SFC composites are therefore promising materials for use in structural applications and should be ideal for high strength structures where SFC is used in the host structure. © 2006 Elsevier B.V. All rights reserved.